Gay Lingo in the Philippine context - Sison, Ma. Elisa L. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1999)
During the sixties, Gay Lingo, then known as Sward peak, emerged in the Philippines as a consequence to the gender prejudice that gays and lesbians were subjected to. The primary objective of the gays, who introduced the language, at that time was to be aware of and consequently assert their sexuality. Today, after a period of almost forty years, the meaning of most gay terms have been revealed and are now widely used by the heterosexual-ruled society. The first anthology of Gay literature, supposedly the primary means to develop and spread Gay Lingo, may have been launched only recently (in 1994), but there have been other effective means of disseminating the language. On television, homosexual and heterosexual speakers of Gay Lingo are seen on a daily basis leaving the general public open to its use. Gay writers in the newspaper and tabloid magazines, whose thousands of circulation are not intended for homosexual readers alone, cannot avoid the use of their own Lingo in writing their articles. And, what appears to be the most effective way of legitimizing Gay Lingo comes from the unconscious effort of the community of bakla or over gays. these individuals have been brave to admit their sexuality not only with the way they act (as reflected by their being effeminate) or dress up, but also in their manner of speaking. They are the ones every heterosexual Filipino gets the first hand exposures to Gay Lingo. Despite all these, gender prejudice still exists. The reason is much of homosexual's set of beliefs particularly that of the gays' remain a dilemma. Although their language has become more and more popular, only few have really attempted to probe deeper into their ideology in order to understand them better. This ignorance, as proposed by Bloomfield, is to be blamed for the perpetuity of prejudice. Currently, there is a need to understand the ideology of gays. Such ideology is accessible using Fowler's assumption of language in his book Linguistic Criticism. In the said book, Fowler defines language as ideology. Hence, the control of curent discrimination lies in the understanding of gay's ideology through their language--Gay Lingo.
Thesis (Bachelor of Arts in English Studies)--University of the Philippines Diliman.